Characteristics and outcomes among patients with need for early dialysis after lung transplantation surgery. Issue 11 (15th October 2017) - Banga, Amit; Mohanka, Manish; Mullins, Jessica; Bollineni, Srinivas; Kaza, Vaidehi; Tanriover, Bekir; Torres, Fernando
Abstract: Background: With the introduction of lung allocation score (LAS), increasingly sicker patients are undergoing lung transplantation (LT). This study was conducted to determine the time trends in need for dialysis after LT, identify variables independently associated with need for dialysis, and evaluate its association with 1‐ and 5‐year mortality. Methods: We queried the United Network of Organ Sharing database for adult patients undergoing LT between 1994 and 2014. We excluded patients with simultaneous dual organ transplantation and where data regarding the need for dialysis were not available. Results: Time trends in the yearly incidence of the need for dialysis showed a gradual increase ( P  = .012). In the post‐LAS era, ethnicity, underlying diagnosis, estimated GFR <90 mL/min/1.73 m 2 and mean pulmonary pressures>35 mm Hg, ventilator or extracorporeal membrane oxygenation support at LT, and >20% increase in serum creatinine between listing and match were independently associated with the need for dialysis. Patients with need for dialysis had significantly increased hazard of 1‐year (n = 13 849; adjusted hazard ratio, 95% CI:7.23, 6.2‐8.4, P  < .001) and 5‐year mortality (n = 7287; adjusted hazard ratio, 95% CI:3.96, 3.43‐4.56, P  < .001). Conclusions: There is a gradual increase in the incidence of the need for early dialysis after LT, and these patients have significantly worse early and late survival. Several pre‐transplant recipient characteristics are independently associated with the need for dialysis.